Role of the doctrine of legal customs in the formation of European law in the Middle Ages - Komnatnaya, Yulia; Miroshnikov, Evgeny; Saveleva, Irina; Bidova, Bela; Boltenkova, Yulia (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of this article is to analyze the medieval legal doctrine of legal customs as a source of law. The author uses comprehensive historical analysis based on traditional scientific cognition methods for jurisprudence, such as analysis, synthesis, deduction, and induction. The issues of the correlation of legal custom and law in Europe in various periods of the Middle Ages, the influence of customary law on the formation and development of substantive and procedural law, as well as the formation of civil and commercial legislation in European countries, are discussed. The research method used is a qualitative research method with a literature and legislation approach. The research results state that understanding of custom developed during the Middle Ages, leading to its recognition as an independent source of law on a par with statutory regulations.